Clonal replacement and expansion among invasive meningococcal isolates of serogroup W in France. Issue 2 (February 2018) - Hong, Eva; Barret, Anne-Sophie; Terrade, Aude; Denizon, Mélanie; Antona, Denise; Aouiti-Trabelsi, Myriam; Deghmane, Ala-Eddine; Parent du Châtelet, Isabelle; Levy-Bruhl, Daniel; Taha, Muhamed-Kheir
Highlights: Neisseria meningitidis group W is currently increasing in Europe and in France. Previous increases in France were linked to the Hajj and to travel to Africa. Whole genome sequencing was used to characterise W isolates in France in 2010–2016. The "UK 2013-strain" has recently expanded in adults aged 15 years and over. A high case fatality rate was observed among cases caused by the "UK 2013-strain". Summary: Background: Neisseria meningitidis group W (NmW) belonging to the clonal complex ST-11 (NmW/cc11) spread in Europe and in France in 2000 and declined thereafter. In France, invasive meningococcal disease (IMD) due to NmW increased again in 2012 and thereafter since 2015. Several sub-lineages of NmW/cc11 are circulating worldwide with successive epidemic waves. We aimed to describe recent epidemiological trends of NmW in France and to explore the microbiological and epidemiological characteristics associated with different NmW/cc11 sub-lineages. Methods: The epidemiology of NmW was described based on data collected through mandatory notification of IMD and strain typing data for culture-confirmed and PCR-confirmed cases for the period 2000–2016. All culture-confirmed cases due to NmW from the period 2010–2016 were characterised by whole genome sequencing (WGS). A detailed epidemiological analysis was performed for culture-confirmed cases on the basis of WGS data. Findings: During the period 2010–2016, genotyping was obtained for 148 cases including all the 132 culture-confirmed cases, among which 127 were matched with epidemiological data, and 16 PCR-confirmed cases (out of a total of 47 PCR-confirmed cases). An increase in IMD was observed in 2012 and was linked to isolates belonging to the "Anglo-French-Hajj" sub-lineage. These isolates have decreased significantly since 2013 and have been replaced by NmW/cc11 isolates related to the "South American – UK" sub-lineage which caused a marked increase in the number of cases of NmW in 2016. In this sub-lineage, the "original UK strain" was first detected in 2012 and increased thereafter, followed by the recently described "UK 2013-strain". Isolates related to the "South American-UK" sub-lineage represented 45% of all NmW cultured isolates from the whole period 2010–2016 but were the most frequent isolates in 2016, representing 76% of the total NmW typed isolates and 94% of the typed NmW/cc11 isolates. A changing pattern in the epidemiology of NmW has been observed in 2015–2016 in relation to the spread of the "UK 2013-strain" with a sharp increase in the number of cases among persons aged 15 years and over and a high case fatality rate (CFR). Among cases due to the "UK 2013-strain", 94% of cases were aged 15 years and over and the CFR was 28%. Interpretation: Our data suggest a recent clonal replacement among NmW/cc11 isolates with the expansion of the "South American-UK" sub-lineage in France and particularly the "UK 2013-strain" which was predominant in 2015 and 2016. A shift in the age-distribution of IMD due to NmW to older ages and the high CFR are consistent with the expansion of a new virulent clone in a naive population. These data may have an impact on tailoring vaccination strategies against NmW.